Comparative Productivity: The USSR, Eastern Europe, and the West - Bergson, Abram (American Economic Review, 1987)
This paper compiles comparative measures of output per worker in 1975 in four socialist and seven Western mixed-economy (WME) countries, and explores sources of observed differences between the two groups of countries in that regard. Such differences seem explicable only partially by reference to differences in per worker capital stock and farm land. A residual disparity of 25-34 percent in favor of WME countries appears to testify to superior efficiency in the latter.